Single-cell and spatial transcriptomics identify COL6A3 as a prognostic biomarker in undifferentiated pleomorphic sarcoma - Jason C. Klein; Lei Wang; Douglas Strand; Chewlan Lastufka; Gregory A. Hosler; Gary C. Hon (Molecular Cancer)
Abstract Undifferentiated pleomorphic sarcoma (UPS) and related tumors are the most common type of soft tissue sarcoma. However, this spectrum of tumors has different etiologies with varying rates of metastasis and survival. Two dermal-based neoplasms in this class of pleomorphic sarcomas, atypical fibroxanthoma (AFX) and pleomorphic dermal sarcoma (PDS), are challenging to differentiate at initial biopsy but vary significantly in prognosis. We performed single-cell transcriptomics on five AFX and PDS biopsy specimens as well as both single-cell and spatial transcriptomics on one PDS excision specimen to better characterize these tumors. The top differential genes between AFX and PDS were predictive of overall survival in 17 other cancers included in the Human Protein Atlas. Of these genes, COL6A3 and BGN predicted overall survival and metastasis-free survival in independent cohorts of 46 and 38 UPS tumors, respectively. COL6A3 was most predictive of overall survival in UPS patients and outperformed an established sarcoma prognostic gene panel at predicting metastasis in UPS.